The Digital Divide in Canada and the U.S.: Measurement and Meaning - Dowding, Martin R. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Since the advent of the Information Highway (Society/Economy) considerable policy-making has been undertaken by governments in Canada and the U.S. in response to the Digital Divide. While measuring the divide has largely been limited to neo-liberal economic analysis, the U.S. appears to be committing more resources and doing more fine-grained analyses of the situation. This paper compares statistical and political economic analyses already completed and provides alternative analyses useful to guarantors of access to information. Depuis l’avènement de l’autoroute de l’information (Société/Économie), un nombre considérable de politiques ont été élaborées par les gouvernements du Canada et des États-Unis afin de réduire le fossé numérique. Alors que la mesure du fossé a été limitée en grande partie par l’analyse économique néo-libérale, les États-Unis semblent engager davantage de ressources et effectuer des analyses plus précises de la situation. Cette étude compare les analyses statistiques et politico-économique déjà achevées et présente des analyses alternatives utiles garantissant l’accès à l’information.